AB0253 The association of the IL1B and TNFα gene polymorphism with juvenile arthritis. (23rd January 2014) - Malievsky, V.A.; Victorova, T.V.; Danilko, K.V.; Nazarova, L.
Abstract : Background: The juvenile (idiopathic) arthritis (JIA) is one of the most common groups of pediatric rheumatic diseases. JIA, as defined by the ILAR, include 7 disease subtypes. Both genetic and environmental factors have been shown to be associated with JIA. Cytokine gene loci are one of the potential susceptibility factors in many immune-inflammatory diseases, such as juvenile arthritis. And patients with JIA had, irrespective of their subclassification, significantly higher levels of pro-inflammatory cytokines. Objectives: The goal of the study was to examine evidence for association of the four cytokine genes single nucleotide polymorphisms (SNPs) with different subtypes of JIA. Methods: A case-control association study was performed, using tagging SNP approach. DNA of 189 unaffected controls and 103 patients with JIA (32 RF-polyarthritis, 41 persistent oligoarthritis, and 30 other JIA subtypes) from Bashkortostan, Russia, was genotyped for IL1B -511 (rs16944), IL10-592 (rs1800872), TNFA -308 (rs1800629) and LTA +252 (rs909253) SNPs by polymerase chain reaction-restriction fragment length polymorphism method. Results: The genotypes distribution was in Hardy-Weinberg equilibrium for all polymorphic genes. The frequencies of LTA and IL10 genotypes investigated did not differ significantly between all affected and control individuals. Variations in genotype frequency were observed between cases and controls for both TNFA and IL1B genes. The TNFA GG and IL1B CC genotypes were prevalence in JIA group (p=0, 005, OR=2, 534 95%CI 1, 299-5, 001 and p=0, 042, OR=1, 781 95%CI 1, 025-3, 096, correspondingly). And TNFA AG genotype was less frequent in JIA patients (p=0, 018, OR=0, 449 95%CI 0, 227-0, 881). Then the JIA individuals were divided in 3 groups: RF-polyarthritis (RFP), persistent oligoarthritis (PO) and others. The distributions of genotypes in RFP and PO groups were similar with overall JIA patients, but the differences with control were not considerable, due to small number of individuals. On the other hand IL1B CC genotype and C allele were associated with high risk of only PO, not with RFP, (pcor =0, 028, OR=2, 671 95%CI 1, 256-5, 691 and pcor =0, 040, OR=1, 989 95%CI 1, 149-3, 462, correspondingly). Conclusions: These findings demonstrate the association of TNFA -308 polymorphism with susceptibility to juvenile (idiopathic) arthritis, and high risk of the persistent oligoarthritis inIL1B -511common SNP variants carriers from Bashkortostan, Russia. These results might have prognostic value for future clinical observations. References: Prahalad S., Glass D. A comprehensive review of the genetics of juvenile idiopathic arthritis. Pediatric Rheumatology. 2008; 6 (11). De Jager W. et all. Blood and synovial fluid cytokine signatures in patients with juvenile idiopathic arthritis: a cross-sectional study. Ann. Rheum. Dis. 2007; 66:589–598. Woo P., Colbert R.A. An overview of genetics of paediatric rheumatic diseases. Best Pract. Res. Clin. Rheumatol. 2009; 23(5):589-97. Disclosure of Interest: None Declared